Pod Hardness, Porosity, and Seed Viability Levels of Several Peanut Varieties - Siti Muzaiyanah; Trustinah Trustinah; Sutrisno Sutrisno (Jurnal Ilmu Pertanian Indonesia, 2025)
The peanut pod shell is composed of cellulose, lignin, and hemicellulose. It has pore channels that can give the seeds direct contact with the environment, resulting in the seeds quickly deteriorating due to temperature fluctuations. This research aims to determine the porosity of the pod shell of several peanut varieties, its relationship with the level of shell hardness, and its effect on seed deterioration that is indicated by seed viability. The research was designed using a randomized block factor design, with the first factor being the type of variety, consisting of Kidang, Hyphoma 3, Landak, Talam 1, Tasia 1, and Takar 1. The second factor was the length of storage, consisting of 1, 2, 3, and 4 months, in quadruplicates, and the hardness of the pods was measured using a digital grain hardness tester meter. Porosity (P) was determined using the volume method. Viability testing includes germination viability (GV), germination rate (GR), and germination rate index (GRI). Pod hardness had a low correlation (r = 0.43) with pod thickness and had no effect on shell porosity level; however, pod porosity level had a strong negative correlation (r = -0.75) with pod shell thickness. Pod shell porosity, GR, and GRI have an influence on seed germination following the regression equation GR = 145-1.85P - 0.41VG+29.93GRI with a coefficient of determination R2 = 0.50, meaning that these variables only have a contribution of 50% and other factors influence the other 50%. The shell thickness affects the level of seed germination. The Tasia and Landak varieties with a shell thickness of >0.75 mm produced lower porosity levels and had the least deterioration seed than the other four varieties. Keywords: germination viability, peanuts, pod hardness, porosity